Implementasi Kebijakan Penanganan Stunting di Indonesia dan Filipina - Truna, Laras Pujaswari; Ginting, Aldo Nathanael R; Sumaryadi, Maritza Hasnadia; Alhaq, Reisya Tepi; F, Fienaurisilmi; Hibatullah, Wan Fairuz Arkan; Afifah, Dian Fitriani (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Indonesia and the Philippines are two countries located in the Southeast Asian region with various similarities, such as social, economic, and geographical conditions. Based on these similarities, both countries face similar challenges, which is stunting. In 2023, the prevalence rate of stunting in Indonesia reached 17.8 percent while in the Philippines it reached 26.7 percent. The prevalence of stunting is caused by many factors, both internal (society behavior) and external (state conditions and applicable policies). The author uses a descriptive qualitative research method through literature studies in comparing the steps of the two countries in reducing the prevalence rate of stunting, starting from the implementation of applicable policies to the programs carried out. Based on the data obtained by the author, Indonesia seeks to implement policies and programs in a decentralized manner while the Philippines implements them in a centralized manner. That way, if the policies in Indonesia and the Philippines are exchanged and implemented, it seems that the Philippines will experience a rapid decline in the prevalence rate of stunting. Meanwhile, if Indonesia implements a policy like in the Philippines, the impact will not be as big as expected, considering the large difference in the size of the country and the policies in the Philippines which are improvements to the policies in Indonesia.